A mouse model of early sporadic tau pathology induces neurogenic plasticity in the hippocampus - Alyssa M. Ash; Sue Rim Baek; Peyton Holder; Sara Singh; Nicholas P. Vyleta; Matthew Willman; Kevin R. Nash; Jason S. Snyder (PLoS ONE, 2025)
Alzheimer’s disease varies by sex but is broadly characterized by widespread neurodegeneration and the accumulation of insoluble amyloid plaques and neurofibrillary tangles. However, at the earliest stages of the disease cell death and pathological tau are localized to the entorhinal cortex. In particular, the lateral entorhinal cortex, and its functions in object-related memory, are among the most vulnerable in aging. Notably, the entorhinal cortex projects directly to the dentate gyrus subregion of the hippocampus, where neurogenesis proceeds throughout adult life. Immature, adult-born neurons provide plasticity at the entorhinal-dentate pathway and they may be uniquely responsive, or vulnerable, to early entorhinal tau pathology. To test this, we injected a human tau-expressing recombinant adeno-associated virus (hTau) into the lateral entorhinal cortex and used male and female AsclCreER mice to birthdate downstream dentate neurons born in early postnatal development or adulthood. Consistent with known roles in neurodegeneration, lateral entorhinal hTau expression caused a loss of mushroom spines in downstream dentate gyrus neurons of male and female mice and reduced dendritic complexity of adult-born neurons in male mice. Presynaptic hTau also increased neurogenesis levels and increased the density of thin spines on adult-born neurons in both male and female mice. Consistent with spine addition, hTau increased the slope of the synaptic input-output curves; amongst adult-born neurons, this was due to a specific effect on synapses in male mice. hTau did not alter the magnitude of long-term potentiation at entorhinal synapses onto adult- or developmentally-born neurons. Thus, in a novel model of early sporadic tau pathology, there are changes consistent with neurodegeneration but also compensatory neuroplastic changes, caused in part by neurogenesis. Since immature neurons have also been identified in the human dentate gyrus, a similar neurogenic plasticity may help maintain entorhinal-hippocampal formation in pathological aging.